Case Report: Right aortic arch with isolation of left brachiocephalic artery and ventricular septal defect - Wang, Gang; Wang, Jieqiong; Zhang, Hongjie; Wang, Hui; Meng, Qiang; Song, Linhong; Zhou, Gengxu (Frontiers in Cardiovascular Medicine, 2024)
Right aortic arch with isolation of left brachiocephalic artery is a rare congenital aortic arch anomaly. Herein,we reported a case of this rare anomaly with ventricular septal defect in a 9-month-old infant. We successfully reconstructed the islolated left brachiocephalic artery and repaired the ventricular septal defect in one stage.